ARHGAP11A Promotes the Malignant Progression of Gastric Cancer by Regulating the Stability of Actin Filaments through TPM1. (6th December 2021) - Guan, Xiaoying; Guan, Xiaoli; Qin, Junjie; Qin, Long; Shi, Wengui; Jiao, Zuoyi
Abstract : The mechanism underlying the poor prognosis of gastric cancer, including its high degree of malignancy, invasion, and metastasis, is extremely complicated. Rho GTPases are involved in the occurrence and development of a variety of malignant tumors. ARHGAP11A, in the Rho GTPase activating protein family, is highly expressed in gastric cancer, but its function and mechanism have not yet been explored. In this study, the effect of ARHGAP11A on the occurrence and development of gastric cancer and the mechanism related to this effect were studied. The expression of ARHGAP11A was increased in gastric cancer cells and tissues, and high ARHGAP11A expression in tissues was related to the degree of tumor differentiation and poor prognosis. Moreover, ARHGAP11A knockout significantly inhibited cell proliferation, cell migration, and invasion in vitro and significantly inhibited the tumorigenic ability of gastric cancer cells in nude mice in vivo. Further studies revealed that ARHGAP11A promotes the malignant progression of gastric cancer cells by interacting with TPM1 to affect cell migration and invasion and the stability of actin filaments. These results suggest that ARHGAP11A plays an important role in gastric cancer and may become a useful prognostic biomarker and therapeutic target for gastric cancer patients.